Program Kemitraan Masyarakat untuk Meningkatkan Kepedulian Masalah Kualitas Rumah Tidak Layak Huni Di Desa Wineru Kecamatan Likupang Timur Kabupaten Minahasa Utara: Community Partnership Program to Increase Awareness of the Problem of the Quality of Uninhabitable Houses in Wineru Village, East Likupang District, North Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Wineru village is located in East Likupang sub-district, North Minahasa district, North Sulawesi province. Wineru village has an area of 750 hectares. Currently, Wineru village is undergoing a lot of construction, especially the construction of houses. The main objective of this service is the construction of permanent concrete houses that are livable or in accordance with the government program called Rumah Layak Huni (RLH). The availability of livable houses for the people of Wineru Village can be done by following the principles of RLH development in accordance with government guidelines. Starting from the planning process, implementation, to evaluation. All of these stages must be carried out following the guidelines issued by the government through the Ministry of Public Works and Housing. Thus the people of Wineru village got a good understanding of the program to improve the quality of uninhabitable houses to meet health and safety standards, so that the community is ready to implement the program in due time. It is hoped that there will be a follow-up to this activity with further activities as a sustainable stage towards clean, healthy and safe settlements for living.